Penggunaan Limbah Abu dalam Pengolahan Telur Asin untuk Mengurangi Risiko Gondok melalui Pengendalian Konsumsi Yodium - Nathania Dwi Damayanti; Annisa Nadya Salsa Amara; Afifah Ananda Nafirah; Muwafiq Adibah; Auliya Aenul Hayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Iodine deficiency remains a major health issue, especially in highland regions like Cisukadana Village, leading to an increased risk of goiter that affects metabolism and growth. This study explores an alternative method to improve iodine intake through the use of factory ash waste in salted egg processing. Factory ash waste is known to contain microelements such as iodine, calcium, and magnesium, which can enhance the nutritional value of salted eggs. The research consisted of three stages: community counseling on iodine importance, practical training on making salted eggs using a salt and ash mixture, and product distribution for evaluation. Eggs were soaked in a brine solution mixed with ash waste for 8–10 days to ensure iodine absorption. The results showed that this method increased iodine content in the eggs, extended shelf life, and improved texture and taste. The program positively impacted the community in health (goiter prevention), social (community involvement and student participation), and economic (potential new business using local resources) aspects. This innovation demonstrates a sustainable approach to enhancing iodine intake while reducing industrial waste impact.